Ceramic rock plate with hydrophobic self-cleaning function and manufacturing method
Through the linked regulation of the formula of ceramic rock blasting and firing system with low crystal silica content, combined with the preparation of hydrophobic self -cleaning coating, the ceramic rock plate absorbs the containment and high crystal silicon oxide content in the humid environment. The problem of cracking of silicon disease and cold processing has realized the hydrophobic self -cleaning function and processability of ceramic rock plates.
Patent Information
- Application Number
- CN202411321878.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Existing ceramic rock slabs are prone to adsorbing stains in humid environments, and high crystalline silica content leads to high risk of silicosis and cold-work cracking, increasing manufacturing costs.
Through the innovative design and co -firing system of ceramic rock blanking systems with low crystal silica content, and high -efficiency adjustment systems, the crystalline silicon content on the surface of the ceramic rock plate surface is reduced, and self -cleaning coating on the surface is prepared on the surface.
The hydrophobic self -cleaning function on the surface of the ceramic rock plate is realized, the risk of silicon lung disease and cold processing cracking consumption, and improved the processability and durability of the ceramic rock plate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building ceramics, and in particular to a ceramic rock plate with a hydrophobic and self-cleaning function and a manufacturing method thereof, and in particular to an environmentally friendly ceramic rock plate with a low crystalline silicon dioxide content and a hydrophobic and self-cleaning function and a manufacturing method thereof. Background Art
[0002] Compared with traditional porcelain tiles, ceramic rock slabs, as a new type of ceramic decorative product in recent years, have the characteristics of large specifications, fewer seams, better density, stronger mechanical properties, richer and more realistic surface textures, etc. Therefore, ceramic rock slabs have a wider range of applications than traditional porcelain tiles. They can not only be used as wall and floor tiles, but also as a multifunctional decorative material. Through secondary processing such as cutting and drilling, they can be made into different shapes and specifications and used in different areas of the home such as dining tables, coffee tables, wardrobes, cabinet doors, background walls, etc.
[0003] Ceramic rock panels are composed of a mixture of inorganic oxides that have been sintered at high temperatures. The wettability of their untreated surfaces is usually hydrophilic. As a widely used decorative material, their natural hydrophilicity makes them very easy to absorb particulate matter such as oil, water, and dust in the air when used in humid, complex and changeable environments such as bathrooms, kitchens, and building exterior walls, which makes it very easy for them to accumulate stains, breed bacteria, and mold on the surface of ceramic rock panels. In order to solve the problem of dirt absorption on the surface of ceramic rock panels, in the actual manufacturing of ceramic rock panels, a layer of organic silicon coating is applied to the surface of the polished ceramic rock panels to achieve the hydrophobic effect on the surface of the ceramic rock panels. However, this coating is easily damaged and the anti-fouling performance gradually weakens as the ceramic rock panels are used for a longer time, and finally loses the hydrophobic self-cleaning function.
[0004] In addition, the current ceramic rock slab blanks use quartz, clay, and feldspar as the main raw materials. The weight percentage of crystalline silicon dioxide in the physical composition of these raw materials is generally 20%-40%, while the weight percentage of crystalline silicon dioxide in the physical composition of the manufactured ceramic rock slab products is generally higher than 10%. Whether in the early stage of ceramic rock slab blank raw material processing or the later stage of ceramic rock slab product cutting, grinding and other processing, a large amount of high crystalline silicon dioxide content respirable dust will be generated. This dust can be deposited in the lungs, causing characteristic inflammatory reactions, extensive nodular fibrosis of lung tissue, and aggregation into fiber clumps, which is commonly known as silicosis. At the same time, it is accompanied by emphysema and bullae, making the ceramic industry a high-risk industry for silicosis. In addition, since the birth of ceramic rock slabs, the entire ceramic rock slab industry has had the phenomenon of cracking during late cold processing, with losses reaching 5%-8%. This is one of the main reasons why the manufacturing cost of ceramic rock slabs has remained high, and has become a major pain point in the industry, restricting the application of ceramic rock slabs in many fields and affecting their promotion and future development. The main reason for this phenomenon is that more crystalline silica is introduced into the raw materials and the crystalline silica undergoes a crystal transformation during the firing process, generating greater stress. Also, because the specifications of ceramic rock slabs are large, the absolute value of the residual stress after cooling is also large, which makes it easy to crack during the manufacturing, cutting and processing processes.
[0005] Based on this, the present invention provides an environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic self-cleaning function and a manufacturing method, which gives the surface of the ceramic rock slab good hydrophobic self-cleaning function, and achieves a significant reduction in the crystalline silica content in the dust generated in the ceramic rock slab manufacturing process, as well as a significant reduction in the crystalline silica content in the phase composition of the green layer of the manufactured ceramic rock slab, thereby effectively reducing the risk of contracting silicosis during the manufacturing and processing of the ceramic rock slab, and at the same time reducing the stress generated in the ceramic rock slab due to the crystal transformation of silica, thereby improving the machinability of the ceramic rock slab, thereby reducing the loss caused by cracking in the later cold processing of the ceramic rock slab. Summary of the invention
[0006] In order to solve the problems of high risk of silicosis caused by high crystalline silica content in the existing ceramic rock slab manufacturing and processing, as well as high breakage rate during later cold processing, and to give the ceramic rock slab surface good hydrophobic self-cleaning function and solve the problem of dirt absorption on the ceramic rock slab surface, the present invention provides an environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic self-cleaning function and a manufacturing method.
[0007] The present invention realizes efficient regulation of the ceramic rock blank formulation system by innovatively designing the low crystalline silicon dioxide content and linking the firing system, so as to minimize the introduction of crystalline silicon dioxide SiO2 into the raw materials of the ceramic rock blank formulation. 2 (Cr ), on the other hand, a small amount of crystalline silicon dioxide SiO 2 (C r ) During the sintering process of the slab body, as much as possible is converted into amorphous silicon dioxide and silicon dioxide that exists as a component in other crystalline phases except crystalline silicon dioxide. Amorphous silicon dioxide belongs to the glass state, wrapped on the surface of some crystalline phases (calcium feldspar, albite, mullite, cordierite, corundum, etc.), and together with other glass phases and gas phases, it constitutes the microstructure of the ceramic slab body, and the crystalline silicon dioxide SiO 2 (C p ) is reduced from the content in weight percentage to 10% or less, which can effectively reduce the risk of silicosis during the manufacturing, polishing, cutting and other processes of ceramic rock slabs. In addition, the stress generated by the crystal transformation of silicon dioxide during the firing process of crystalline silicon dioxide is reduced, and the residual stress of the finished ceramic rock slab is small, which makes the rock slab easy to process and reduces the loss caused by cracking during the later cold processing. The present invention also prepares a hydrophobic self-cleaning coating on the upper surface of the decorative layer of the ceramic rock slab by using fluorine-free material aluminate solid and anhydrous ethanol as raw materials, thereby giving the surface of the ceramic rock slab a good hydrophobic self-cleaning function. The formed coating reduces the solid surface energy of the upper surface of the decorative layer, thereby increasing the contact angle between the water droplets and the ceramic rock slab, making it difficult for the water droplets to adhere to the surface of the ceramic rock slab but slide along the surface of the ceramic rock slab and take away the pollutants on the surface, thereby keeping the surface of the ceramic rock slab dry and clean.
[0008] In a first aspect, the present invention provides an environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic self-cleaning function.
[0009] A low-crystalline silicon dioxide content environmentally friendly ceramic rock plate with hydrophobic self-cleaning function, comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, wherein the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) is ≤10% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is >90°.
[0010] The phase composition refers to the content of the crystalline phase, glass phase and gas phase in the ceramic rock slab body layer by weight percentage. The crystalline phase is the dominant phase that determines the basic performance of the ceramic rock slab, including crystalline silica, calcium feldspar, albite, mullite, cordierite, corundum, etc. Its type, content, existence, etc. will affect the performance of the ceramic rock slab; the glass phase refers to the low-melting component in the ceramic rock slab body layer, and its content, distribution, etc. will affect the performance of the ceramic rock slab; the gas phase (pores) is inevitable in the manufacturing process of the ceramic rock slab, and generally has a very small content in the ceramic rock slab body layer. Its existence, content, and distribution state also affect the performance of the ceramic rock slab.
[0011] In this application, crystalline silicon dioxide refers to silicon dioxide in the form of a crystalline phase in the physical composition of a ceramic slab raw material or a ceramic slab blank layer, wherein silicon dioxide in the form of a crystalline phase in the physical composition of a ceramic slab raw material is denoted as SiO 2 (C r ); Silicon dioxide in the form of a crystalline phase in the phase composition of the ceramic rock slab green body layer is denoted as SiO 2 (C p ).
[0012] As a further solution, the chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 58%-65%, Al 2 O 3 22%-28.5%, Fe 2 O 3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K 2 O 1.5%-5%, Na 2 O 0.35%-3%, the remainder is impurities.
[0013] In this application, SiO 2 (T) refers to the sum of silicon dioxide existing in the crystalline phase in the ceramic rock slab green body layer, silicon dioxide existing in the glass phase, and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide.
[0014] As a further solution, the decorative layer is made by any one or a combination of porcelain polishing process, glaze polishing process, dry particle polishing process, glue dry particle process, digital mold process, fine or coarse matte dry particle surface process, peeling glaze / ink or sinking glaze / ink process.
[0015] Specifically, the porcelain polishing process mainly includes the following steps: preparing a ceramic rock slab blank; applying slurry and / or penetrating ink; firing; and soft polishing.
[0016] Specifically, the glaze polishing process mainly includes the following steps: preparing a ceramic rock slab blank; applying cosmetic soil and / or glaze; performing inkjet printing, screen printing or roller printing; applying protective glaze and polishing glaze or only applying polishing glaze; firing; and hard polishing.
[0017] Specifically, the dry granular polishing process mainly includes the following steps: preparing a ceramic rock slab body; applying cosmetic soil and / or glaze; performing inkjet printing, screen printing or roller printing; applying and polishing dry granular glaze; firing; and hard polishing.
[0018] Specifically, the glue dry granulation process mainly includes the following steps: preparing a ceramic rock slab body; applying cosmetic soil and / or glaze; performing inkjet printing, screen printing or roller printing; applying glue dry granules; firing; and brush polishing.
[0019] Specifically, the digital mold process mainly includes the following steps: preparing a ceramic rock slab blank; applying cosmetic soil and / or glaze; printing digital mold glaze / ink; performing inkjet printing, screen printing or roller printing; applying polishing glaze and one of protective glaze, polishing glaze, polishing dry granule glaze, fine / coarse matte dry granules, and glue dry granules; firing; performing one of brush polishing, soft polishing, hard polishing, or no polishing.
[0020] Specifically, the fine or coarse matte dry grain surface process mainly includes the following steps: preparing a ceramic rock slab body; applying cosmetic soil and / or glaze; performing inkjet printing, screen printing or roller printing; applying fine or coarse matte dry grain glaze; firing and soft polishing.
[0021] Specifically, the peeling glaze / ink or sinking glaze / ink process mainly includes the following steps: preparing a ceramic rock slab blank; applying cosmetic soil and / or surface glaze; printing peeling glaze / ink or sinking glaze / ink; performing inkjet printing or screen printing or roller printing; applying polishing glaze and one of protective glaze, polishing glaze, polishing dry granule glaze, fine / coarse matte dry granules, and glue dry granules; firing; performing one of brush polishing, soft polishing, hard polishing, or no polishing.
[0022] As a further solution, when the decorative layer is made by a combination of porcelain polishing process, glaze polishing process, dry particle polishing process, glue dry particle process, digital mold process, fine or coarse matte dry particle surface process, peeling glaze / ink or sinking glaze / ink process, the process used needs to be adaptively adjusted accordingly.
[0023] As a further solution, in the hydrophobic self-cleaning coating solution for forming the hydrophobic self-cleaning coating, the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:(5-15).
[0024] Specifically, the aluminate solid is one of diisopropyl di(acetylacetonato)aluminate and isopropyl distearoyloxyaluminate or a combination thereof.
[0025] The static water contact angle refers to the angle between one side of the tangent line on the water drop side and the solid-liquid boundary line when a drop of water is statically located on the solid surface and the gas-liquid interface is tangent at the intersection of the gas, water drop and solid. When the static water contact angle is <90°, the surface of the solid is hydrophilic, and the water drop easily wets the solid and spreads on its surface; when the static water contact angle = 90°, the solid surface is neutrally wettable, and the water drop is hemispherical and attached to the solid surface; when the static water contact angle is >90°, the solid surface is hydrophobic, and the water drop is not easy to wet the solid, and tends to remain spherical to reduce the contact area with the solid.
[0026] In the present application, the raw materials for preparing the hydrophobic self-cleaning coating solution for forming the hydrophobic self-cleaning coating are aluminate solid and anhydrous ethanol, the aluminate solid is one or a combination of diisopropyl di(acetylacetonate)aluminate and isopropyl distearoyloxyaluminate, which is soluble in an organic solvent such as anhydrous ethanol, diisopropyl di(acetylacetonate)aluminate and / or isopropyl distearoyloxyaluminate are mixed and dispersed with anhydrous ethanol in a certain proportion, and are evenly sprayed on the upper surface of the decorative layer. After drying and curing, a hydrophobic self-cleaning coating is formed on the upper surface of the decorative layer. The fluidity of the hydrophobic self-cleaning coating solution increases during the drying and curing process, filling The pores on the upper surface of the decorative layer are uniformly spread on the upper surface of the decorative layer. After cooling, they are permanently retained in the pores in a solid form and firmly adhered to the upper surface of the decorative layer to form a hydrophobic self-cleaning coating, which reduces the solid surface energy of the ceramic rock plate surface, thereby reducing the interfacial tension between the water droplets and the surface of the ceramic rock plate, so that the static water contact angle of the water droplets on the surface of the ceramic rock plate increases, which plays a role in hindering the spreading of the water droplets, so that the water droplets cannot stay on the surface of the ceramic rock plate for a long time, but slide along the surface of the ceramic rock plate and take away the pollutants on the surface, so that the surface of the ceramic rock plate remains dry and tidy for a long time, giving the ceramic rock plate a hydrophobic self-cleaning function. The formed hydrophobic self-cleaning coating is firmly combined with the upper surface of the decorative layer, is not easy to be damaged and fall off during use, has good adhesion and high firmness, and is not easy to react with water, oxygen, carbon dioxide, etc. in the air to change color and lose the hydrophobic self-cleaning function, and has good durability. In addition, the raw materials used to prepare the hydrophobic self-cleaning coating solution do not contain fluorine and other components that are harmful to the human body and the environment, and have good environmental protection.
[0027] As a further solution, the static water contact angle of the hydrophobic self-cleaning coating is greater than 90° after a firmness test, the hydrophobic self-cleaning coating does not change color after a durability test, the static water contact angle is greater than 90°, and the static water contact angle is greater than 90° after another firmness test, and the hydrophobic self-cleaning coating passes the pollution resistance test.
[0028] As a further solution, the content of the glass phase in the physical composition of the green body layer is 69.0%-88.5% by weight.
[0029] As a further solution, the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 59.98%-67%, Al 2 O 3 20.82%-27%, Fe 2 O 3 0-2.64%, CaO 0.65%-5.85%, MgO0.57%-6.49%, K 2 O 1.95%-6.26%, Na 2 O 0.5%-3.76%, TiO 2 0-0.78%.
[0030] In this application, SiO 2 (A) refers to the normalized content of amorphous silicon dioxide in the glass phase in the physical composition of the ceramic slab green body layer, expressed as a percentage by weight.
[0031] Specifically, the SiO 2 (A) On the one hand, it comes from the melting of crystalline silica and feldspar during the firing process of the ceramic slab body. On the other hand, it comes from the decomposition products of clay minerals such as kaolin in the raw materials of the ceramic slab body during the firing process of the ceramic slab body.
[0032] As a further solution, the phase composition of the green body layer contains more silicon dioxide SiO2 than the feldspar stoichiometric ratio in the glass phase. 2 The amount percentage of substance (E) is ≥27.0%.
[0033] SiO 2 (E) refers to the percentage of silicon dioxide in the glass phase that exceeds the stoichiometric ratio of feldspar in the physical composition of the ceramic slab green body layer, including the part of crystalline silicon dioxide in the raw material dissolved into the glass phase and the part brought in by the decomposition of clay minerals.
[0034] As a further solution, the phase composition of the green body layer contains n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O)≥0.350.
[0035] In the present application, n(CaO+MgO) refers to the sum of the percentages of CaO and MgO in the glass phase in the physical composition of the ceramic slab blank layer after normalization by the amount of substance; n(CaO+MgO+K 2O+Na 2 O) refers to the phase composition of the ceramic rock slab body layer, CaO, MgO, K in the glass phase 2 O and Na 2 O is the sum of percentages calculated by amount of substance after normalization.
[0036] CaO and MgO are generally used as excellent fluxes in the building ceramics industry, mainly to reduce the maximum firing temperature of the brick and reduce the high-temperature viscosity and surface tension of the melt. This application innovatively designs a low-crystalline silica content ceramic rock slab body formula system with hydrophobic self-cleaning function to improve the alkaline earth metal oxides (CaO and MgO) in the glass network modifier (CaO, MgO, K 2 O and Na 2 O) in the body layer, so that the ceramic rock plate can avoid the phenomenon of raw burning due to too high temperature or over-burning due to too low temperature, and increase the flux of the body layer of the ceramic rock plate, thereby increasing the solubility of glass relative to crystalline silicon dioxide in the physical composition of the body layer during the firing process of the ceramic rock plate, so that the small amount of crystalline silicon dioxide SiO 2 (C r ) is more converted into amorphous silicon dioxide and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide, which effectively reduces the crystalline silicon dioxide SiO in the phase composition of the body layer. 2 (C p ) content, while increasing the content of the glass phase in the physical composition of the green body layer, and subsequently also increasing the amount percentage of silicon dioxide in the glass phase in the physical composition of the green body layer that exceeds the stoichiometric ratio of feldspar.
[0037] As a further solution, the fracture toughness of the environmentally friendly ceramic rock plate with low crystalline silica content and hydrophobic self-cleaning function is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
[0038] As a further solution, the environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic self-cleaning function is processed according to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard to achieve first-level machinability.
[0039] In a second aspect, the present invention provides a method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silica content and hydrophobic self-cleaning function, which comprises the following steps: S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, wherein the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 55.68%-62%, Al 2 O 3 20.5%-27.36%, Fe 2 O 3 0-2.88%, CaO 0.48%-6.52%, MgO 0.47%-4.8%, K 2 O 1.44%-4.8%, Na 2 O 0.33%-2.8%, loss on ignition 4%-7%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150-1250°C, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: uniformly spraying the hydrophobic self-cleaning coating solution prepared in S7 on the upper surface of the semi-finished ceramic rock slab after post-processing in step S6, and then drying and curing the semi-finished ceramic rock slab to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, thereby obtaining a ceramic rock slab finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, wherein the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) is ≤10% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is >90°.
[0040] As a further scheme, in step S7, the hydrophobic self-cleaning coating solution that forms the hydrophobic self-cleaning coating has a ratio of aluminate solid to anhydrous ethanol of 1:(5-15) in parts by weight; the method for preparing the hydrophobic self-cleaning coating solution comprises the following steps: S7a(Ⅰ), aluminate solid crushing: crushing the aluminate solid and sieving it with a 100-mesh sieve to obtain a granular aluminate solid powder less than 150 μm; S7a(Ⅱ), aluminate solid dissolution: mixing the crushed aluminate solid powder with anhydrous ethanol in a certain proportion and stirring until the aluminate solid powder is completely dissolved to prepare a uniform hydrophobic self-cleaning coating solution.
[0041] As a further solution, in step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 5-50 ml / m 2 The drying and curing temperature of the drying and curing treatment is 90-150° C., and the drying and curing time is 15-120 minutes.
[0042] As a further scheme, in step S1, when preparing black ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay A, washed soil A, washed soil B, kaolin A, calcined soil A, potassium feldspar A, potassium feldspar B, potassium sodium feldspar A, potassium sodium feldspar B, wollastonite A, raw talc A, raw talc B, calcined bauxite B, and diopside; when preparing white ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay B, rock mud, kaolin B, calcined soil B, raw talc B, wollastonite A, wollastonite B, potassium feldspar A, potassium feldspar B, talc, TM2106 frit, fused quartz, calcined alumina A, calcined alumina B, bone ash, calcined bauxite A, and calcined bauxite B.
[0043] As a further solution, in step S1, the ball milling system is an intermittent ball milling system or a continuous ball milling system.
[0044] As a further solution, in step S2, before spray-drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0045] Specifically, preheating the ceramic rock slab green body slurry refers to the process of transporting the ceramic rock slab green body slurry to a mud servo tank before the ceramic rock slab green body slurry is spray-dried, and heating the ceramic rock slab green body slurry to above 80°C through the hot air and mud gas / liquid type heat exchanger in the cold section at the tail of the kiln; preheating the ceramic rock slab green body slurry can increase the temperature and fluidity of the ceramic rock slab green body slurry, thereby reducing the energy consumption of the spray drying process in step S2, improving the energy utilization efficiency, increasing the production capacity, and achieving the purpose of energy saving and consumption reduction.
[0046] As a further solution, in step S4, the decoration of the ceramic rock slab body is any one of or a combination of porcelain polishing process, glaze polishing process, dry grain polishing process, fine or coarse matte dry grain surface process, glue dry grain process, digital mold process, peeling glaze / ink or sinking glaze / ink process.
[0047] As a further solution, in step S4, when the decoration of the ceramic rock slab body is a combination of porcelain polishing process, glaze polishing process, dry grain polishing process, fine or coarse matte dry grain process, glue dry grain process, digital mold process, peeling glaze / ink or sinking glaze / ink process, the process used needs to be adaptively adjusted accordingly.
[0048] As a further solution, in step S6, the post-processing includes polishing and edge grinding.
[0049] As a further solution, in step S1, the screening is performed using a 80-150 mesh vibrating screen, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a residue of 2.5%-3.5%, the specific gravity is 1.68-1.74 g / ml, and the flow rate is NK-2 Iwata viscosity cup 16-32s.
[0050] As a further solution, in step S2, the moisture content of the ceramic rock slab green body powder is 5.5%-7.5%, and the particle size is 45%-55% after 40 mesh sieve.
[0051] As a further solution, in step S3, the pressure of the molding equipment during compression molding is 35-42 MPa.
[0052] Residual stress is a key factor affecting the machinability of ceramic rock slabs. Only by reducing the residual stress to the lowest level possible can the risk of cracking of ceramic rock slabs during manufacturing and cutting be reduced, and the manufactured ceramic rock slabs have excellent machinability. Among them, the maximum firing temperature of the ceramic rock slab blank is 1150-1250℃, the firing cycle is 55-150min, and the insulation time at the maximum firing temperature is ≥7min. Compared with traditional porcelain tiles, the insulation time at the maximum firing temperature is extended, and the heating and cooling rates are slowed down. Delaying the heating rate during the firing process of the ceramic rock slab blank and extending the insulation time at the maximum firing temperature are, on the one hand, beneficial to the small amount of crystalline silicon dioxide SiO 2 (C r ) is converted into glass phase and silicon dioxide existing as a component in other crystalline phases except crystalline silicon dioxide, so that the crystalline silicon dioxide SiO 2 (C r) is further reduced; on the other hand, it is beneficial to the oxidation and decomposition of humus in the ceramic rock slab blank, thereby increasing the density of the blank layer and improving the fracture toughness of the ceramic rock slab. Delaying the heating and cooling rates can extend the interval of the crystal phase transformation of crystalline silicon dioxide in the blank layer and make the crystal phase transformation slow and uniform, reduce the volume effect of crystalline silicon dioxide caused by the crystal phase transformation of the ceramic rock slab during the firing process, and completely release the internal stress in the blank layer, thereby effectively reducing the residual stress in the blank layer. In addition, the ceramic rock slab blank itself has a low crystalline silicon dioxide content, and during the firing process, part of the crystalline silicon dioxide is converted into glass phase and silicon dioxide that exists as a component in other crystalline phases other than crystalline silicon dioxide. Therefore, the absolute value of the residual stress of the ceramic rock slab after cooling is also small, and it is not easy to break during manufacturing, cutting and other processes, and has excellent machinability. Refer to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard for processing to achieve first-level machinability.
[0053] As a further solution, the chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 58%-65%, Al 2 O 3 22%-28.5%, Fe 2 O 3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K 2 O 1.5%-5%, Na 2 O 0.35%-3%, the remainder is impurities.
[0054] As a further solution, in step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 69.0%-88.5%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 59.98%-67%, Al 2 O 3 20.82%-27%, Fe 2 O 3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K 2 O 1.95%-6.26%, Na 2 O 0.5%-3.76%, TiO 2 0-0.78%, the glass phase in the phase composition of the green body layer contains more silicon dioxide SiO than the feldspar stoichiometric amount. 2The amount percentage of (E) is ≥ 27.0%, and the phase composition of the green body layer is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O)≥0.350, the static water contact angle of the hydrophobic self-cleaning coating is greater than 90° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is greater than 90°, and the static water contact angle is greater than 90° after the firmness test again, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test.
[0055] As a further solution, the fracture toughness of the environmentally friendly ceramic rock plate with low crystalline silica content and hydrophobic self-cleaning function is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
[0056] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts an innovative design of a low-crystalline silicon dioxide content ceramic rock slab blank formulation system with a hydrophobic self-cleaning function and a highly efficient linkage control of a firing system. At the same time, a fluorine-free material aluminate solid and anhydrous ethanol are used as raw materials to prepare a hydrophobic self-cleaning coating on the upper surface of the ceramic rock slab decorative layer, thereby giving the ceramic rock slab surface a good hydrophobic self-cleaning function. The phase composition of the blank layer of the manufactured low-crystalline silicon dioxide content environmentally friendly ceramic rock slab with a hydrophobic self-cleaning function is crystalline silicon dioxide SiO 2 (C p ) The content by weight percentage is ≤10%, the static water contact angle of the hydrophobic self-cleaning coating is greater than 90°, the hydrophobic self-cleaning coating is not easily damaged or detached during use of the ceramic rock plate, has good adhesion and high firmness, and is not easy to react with water, oxygen, carbon dioxide, etc. in the air to change color and lose the hydrophobic self-cleaning function, and has good durability. The raw materials used to prepare the hydrophobic self-cleaning coating solution do not contain fluorine and other ingredients that are harmful to the human body and the environment. In addition, the crystalline silicon dioxide content in the dust generated during the manufacturing process of the ceramic rock plate is greatly reduced, and the crystalline silicon dioxide content in the phase composition of the green layer of the manufactured ceramic rock plate is greatly reduced, which effectively reduces the risk of silicosis during the manufacturing and processing of the ceramic rock plate, and complies with the national call for green, healthy and environmentally friendly production; (2) The present invention realizes efficient linkage and regulation of the firing system of the ceramic rock slab with low crystalline silica content and hydrophobic and self-cleaning function, so that the small amount of crystalline silica originally brought into the raw materials is further reduced during the firing process of the ceramic rock slab blank. At the same time, the volume effect of the crystalline silica caused by the crystal transformation during the cooling process of the ceramic rock slab is reduced, and the residual stress in the blank layer is reduced. The environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic and self-cleaning function thus obtained has greater fracture toughness and fracture modulus. It is processed according to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard and achieves first-level machinability, which effectively reduces the high loss rate of the rock slab caused by cracking due to later cold processing.
[0057] (3) The present invention preheats the ceramic rock slab green body slurry by means of hot air and mud gas / liquid heat exchanger in the cold section at the rear of the kiln before the ceramic rock slab green body slurry is spray-dried, thereby reducing the energy consumption of the spray drying process, improving the energy utilization efficiency, increasing the production capacity, and achieving the purpose of energy saving and consumption reduction.
[0058] (4) Most of the raw materials used in the manufacture of the environmentally friendly ceramic rock slabs with low crystalline silica content and hydrophobic self-cleaning function in the present invention are raw materials used for conventional ceramic rock slab blanks. It is only necessary to make systematic adjustments to the process parameter configuration based on the existing ceramic rock slab manufacturing line, without the need to add other equipment. The manufacturing process is economical and environmentally friendly, and the process controllability is strong. DETAILED DESCRIPTION
[0059] In order to make the technical solution and advantages of the present invention clearer, the technical solution of the present invention is described more clearly and completely in combination with specific embodiments. In the embodiments, the equipment used is the same as the manufacturing equipment used for conventional ceramic rock panels unless otherwise specified. Example Example 1
[0060] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 55.82%, Al 2 O 3 26.15%, Fe 2 O 31.62%, CaO 1.78%, MgO2.81%, K 2 O 3.72%, Na 2 O 2.48%, loss on ignition 5.26%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1214°C, the firing cycle is 88.9 minutes, and the holding time at the highest firing temperature is 25.0 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T1, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 126.6°.
[0061] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:9.5.
[0062] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 30 ml / m 2 The drying and curing temperature for the drying and curing treatment is 130°C, and the drying and curing time is 65 minutes.
[0063] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium-sodium feldspar A, and potassium feldspar A.
[0064] In step S1 , the ball milling system is a continuous ball milling system.
[0065] In step S4, the ceramic rock slab body is decorated with a fine matte dry grain process.
[0066] In step S6, post-processing includes polishing and edge grinding.
[0067] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.14%, the specific gravity is 1.719 g / ml, and the flow rate is NK-2 Iwata viscosity cup 26s.
[0068] In step S2, the moisture content of the ceramic rock slab green body powder is 6.8%, and the particle size is 51.4% of the 40-mesh residue.
[0069] In step S3, the pressure of the molding equipment during compression molding is 37.5 MPa.
[0070] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 58.92%, Al 2 O 3 27.60%, Fe 2 O 3 1.71%, CaO 1.88%, MgO 2.97%, K 2 O 3.93%, Na 2 O 2.62%, the balance is impurities.
[0071] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 88.50%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.03%, Al 2 O 3 22.10%, Fe 2 O 3 1.57%, CaO 2.12%, MgO 3.36%, K 2 O 4.44%, Na 2 O 2.96%, TiO 2 0.42%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance (E) is 27.1%. The phase composition of the green body layer is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2O) is 0.562, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 123.9°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 124.3°, and the static water contact angle after the firmness test is 122.4°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 2
[0072] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 57.27%, Al 2 O 3 25.93%, Fe 2 O 3 1.63%, CaO 0.83%, MgO1.85%, K 2 O 3.68%, Na 2 O 2.48%, loss on ignition 5.98%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1250°C, the firing cycle is 55.0 min, and the holding time at the highest firing temperature is 23.7 min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T2, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 2.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 158.3°.
[0073] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:5.
[0074] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 50 ml / m 2 The drying and curing temperature for the drying and curing treatment is 150°C, and the drying and curing time is 15 minutes.
[0075] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium-sodium feldspar A, and potassium feldspar A.
[0076] In step S1 , the ball milling system is an intermittent ball milling system.
[0077] In step S4, the ceramic rock slab blank is decorated by a porcelain polishing process.
[0078] In step S6, post-processing includes polishing and edge grinding.
[0079] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.50%, the specific gravity is 1.740 g / ml, and the flow rate is 32s of the NK-2 Iwata viscosity cup.
[0080] In step S2, the moisture content of the ceramic rock slab green body powder is 7.5%, and the particle size is 55.0% of the 40-mesh residue.
[0081] In step S3, the pressure of the molding equipment during compression molding is 35.0 MPa.
[0082] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 60.92%, Al 2 O 3 27.57%, Fe 2 O 31.73%, CaO 0.88%, MgO 1.97%, K 2 O 3.91%, Na 2 O 2.64%, the remainder is impurities.
[0083] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 88.00%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.87%, Al 2 O 3 23.42%, Fe 2 O 3 1.60%, CaO 1.00%, MgO 2.24%, K 2 O 4.44%, Na 2 O 3.00%, TiO 2 0.43%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.436, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 155.1°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 156.5°, and the static water contact angle after the firmness test is 154.7°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 3
[0084] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 60.52%, Al 2 O 3 20.50%, Fe 2 O 3 0%, CaO 6.52%, MgO 0.47%, K 2 O 1.95%, Na 2O 2.80%, loss on ignition 6.82%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1179°C, the firing cycle is 122.9 minutes, and the holding time at the highest firing temperature is 22.4 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T3, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 3.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 97.8°.
[0085] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:13.
[0086] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 11 ml / m 2 The drying and curing temperature for the drying and curing treatment is 100°C, and the drying and curing time is 110 minutes.
[0087] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0088] In step S1 , the ball milling system is a continuous ball milling system.
[0089] In step S4, the ceramic rock slab body is decorated by a glaze polishing process.
[0090] In step S6, post-processing includes polishing and edge grinding.
[0091] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.79%, the specific gravity is 1.697 g / ml, and the flow rate is NK-2 Iwata viscosity cup 21s.
[0092] In step S2, the moisture content of the ceramic rock slab green body powder is 6.1%, and the particle size is 47.9% of the 40-mesh residue.
[0093] In step S3, the pressure of the molding equipment during compression molding is 40.0 MPa.
[0094] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 64.95%, Al 2 O 3 22.00%, Fe 2 O 3 0%, CaO 7.00%, MgO 0.50%, K 2 O 2.09%, Na 2 O 3.00%, the balance is impurities.
[0095] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 87.00%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 66.33%, Al 2 O 3 20.87%, Fe 2 O 3 0%, CaO 5.85%, MgO 0.57%, K 2 O 2.40%, Na 2 O 3.45%, TiO 2 0.53%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.594, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 95.1°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 96.6°, and the static water contact angle after the firmness test is 93.6°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 4
[0096] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 56.17%, Al 2 O 3 26.91%, Fe 2 O 3 2.70%, CaO 2.68%, MgO0.82%, K 2 O 3.40%, Na 2 O 2.18%, loss on ignition 4.90%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1243°C, the firing cycle is 61.8 minutes, and the holding time at the highest firing temperature is 21.1 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T4, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 4.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 155.5°.
[0097] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:5.5.
[0098] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 48 ml / m 2 The drying and curing temperature for the drying and curing treatment is 150°C, and the drying and curing time is 20 minutes.
[0099] In step S1, the raw materials for preparing ceramic rock slab green body slurry are: washed soil A, raw talc A, calcined bauxite B, potassium-sodium feldspar A, potassium feldspar A, and kaolin A.
[0100] In step S1 , the ball milling system is an intermittent ball milling system.
[0101] In step S2, the ceramic rock slab green body slurry obtained in step S1 is subjected to slurry preheating treatment before being spray-dried.
[0102] In step S4, the ceramic rock slab body is decorated by a glaze polishing process.
[0103] In step S6, post-processing includes polishing and edge grinding.
[0104] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.43%, the specific gravity is 1.736 g / ml, and the flow rate is 31s of NK-2 Iwata viscosity cup.
[0105] In step S2, the moisture content of the ceramic rock slab green body powder is 7.4%, and the particle size is 54.3% of the 40-mesh residue.
[0106] In step S3, the pressure of the molding equipment during compression molding is 35.5 MPa.
[0107] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 59.06%, Al 2 O 3 28.30%, Fe 2 O 3 2.84%, CaO 2.82%, MgO 0.86%, K 2 O 3.57%, Na 2 O 2.29%, the balance is impurities.
[0108] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 86.23%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2(A) 60.00%, Al 2 O 3 27.00%,Fe 2 O 3 2.50%, CaO 2.41%, MgO 1.00%, K 2 O 4.14%, Na 2 O 2.66%, TiO 2 0.30%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.439, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 152.2°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 153.1°, and the static water contact angle after the firmness test is 151.9°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 5
[0109] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 58.89%, Al 2 O 3 25.11%, Fe 2 O 3 1.89%, CaO 1.72%, MgO0.97%, K 2 O 4.27%, Na 2 O 2.24%, loss on ignition 4.72%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1236°C, the firing cycle is 68.6 minutes, and the holding time at the highest firing temperature is 19.9 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T5, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 4.5% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 154.6°.
[0110] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:6.
[0111] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 47 ml / m 2 The drying and curing temperature for the drying and curing treatment is 147°C, and the drying and curing time is 20 minutes.
[0112] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: ball clay A, washed soil A, washed soil B, wollastonite A, potassium-sodium feldspar B, raw talc A, potassium feldspar B, calcined bauxite B, and diopside.
[0113] In step S1 , the ball milling system is a continuous ball milling system.
[0114] In step S4, the ceramic rock slab body is decorated by dry granular polishing process.
[0115] In step S6, post-processing includes polishing and edge grinding.
[0116] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.36%, the specific gravity is 1.731 g / ml, and the flow rate is 30s of NK-2 Iwata viscosity cup.
[0117] In step S2, the moisture content of the ceramic rock slab green body powder is 7.2%, and the particle size is 53.6% of the 40-mesh residue.
[0118] In step S3, the pressure of the molding equipment during compression molding is 36.0 MPa.
[0119] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 61.81%, Al 2 O 3 26.36%, Fe 2 O 3 1.98%, CaO 1.80%, MgO 1.02%, K 2 O 4.48%, Na 2 O 2.35%, the balance is impurities.
[0120] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 85.57%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.25%, Al 2 O 3 24.05%, Fe 2 O 3 1.94%, CaO 1.36%, MgO 1.19%, K 2 O 5.24%, Na 2 O 2.75%, TiO 2 0.23%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.350, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 151.3°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 152.7°, and the static water contact angle after the firmness test is 150.4°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 6
[0121] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 60.49%, Al 2 O 3 21.77%, Fe 2 O 3 0.26%, CaO 4.85%, MgO2.49%, K 2 O 3.01%, Na 2 O 1.10%, loss on ignition 5.87%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1186°C, the firing cycle is 116.1min, and the holding time at the highest firing temperature is 18.6min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the ceramic rock slab semi-finished product after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock slab finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T6, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a weight percentage of 6.5%, and the static water contact angle of the hydrophobic self-cleaning coating is 119.3°.
[0122] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:10.5.
[0123] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 25 ml / m 2The drying and curing temperature for the drying and curing treatment is 120°C, and the drying and curing time is 85 minutes.
[0124] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: wollastonite A, raw talc B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, and calcined clay B.
[0125] In step S1 , the ball milling system is an intermittent ball milling system.
[0126] In step S2, the ceramic rock slab green body slurry obtained in step S1 is subjected to slurry preheating treatment before being spray-dried.
[0127] In step S4, the decoration of the ceramic rock slab body is a combination of a digital mold process and a glue dry granulation process.
[0128] In step S6, post-processing includes polishing and edge grinding.
[0129] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.86%, the specific gravity is 1.701 g / ml, and the flow rate is NK-2 Iwata viscosity cup 22s.
[0130] In step S2, the moisture content of the ceramic rock slab green body powder is 6.2%, and the particle size is 48.6% after 40 mesh sieve.
[0131] In step S3, the pressure of the molding equipment during compression molding is 39.5 MPa.
[0132] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 64.19%, Al 2 O 3 23.59%, Fe 2 O 3 0.30%, CaO 4.88%, MgO 2.68%, K 2 O 3.14%, Na 2 O 1.02%, the balance is impurities.
[0133] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 79.41%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 65.53%, Al 2 O 3 21.67%, Fe 2 O 3 0.38%, CaO 3.73%, MgO 3.19%, K2 O 3.95%, Na 2 O 1.28%, TiO 2 0.26%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.700, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 117.3°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 118.6°, and the static water contact angle after the firmness test is 116.3°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 7
[0134] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 59.91%, Al 2 O 3 23.12%, Fe 2 O 3 0%, CaO 4.69%, MgO 1.96%, K 2 O 4.51%, Na 2 O 1.16%, loss on ignition 4.65%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150°C, the firing cycle is 150.0 min, and the holding time at the highest firing temperature is 17.3 min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T7, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a weight percentage of 6.7%, and the static water contact angle of the hydrophobic self-cleaning coating is 92.6°.
[0135] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:15.
[0136] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 5 ml / m 2 The drying and curing temperature for the drying and curing treatment is 90°C, and the drying and curing time is 120 minutes.
[0137] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: rock mud, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, and potassium feldspar A.
[0138] In step S1 , the ball milling system is a continuous ball milling system.
[0139] In step S2, the ceramic rock slab green body slurry obtained in step S1 is subjected to slurry preheating treatment before being spray-dried.
[0140] In step S4, the ceramic rock slab blank is decorated by a porcelain polishing process.
[0141] In step S6, post-processing includes polishing and edge grinding.
[0142] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.50%, the specific gravity is 1.680 g / ml, and the flow rate is 16s of the NK-2 Iwata viscosity cup.
[0143] In step S2, the moisture content of the ceramic rock slab green body powder is 5.5%, and the particle size is 45.0% after 40 mesh sieve.
[0144] In step S3, the pressure of the molding equipment during compression molding is 42.0 MPa.
[0145] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 62.83%, Al 2 O 3 24.25%, Fe 2 O 3 0%, CaO 4.92%, MgO 2.06%, K 2 O 4.73%, Na 2 O 1.21%, the remainder is impurities.
[0146] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 78.80%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 65.18%, Al 2 O 3 21.00%, Fe 2 O 3 0%, CaO 4.08%, MgO 2.21%, K 2 O 6.00%, Na 2 O 1.54%, TiO 2 0%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance (E) is 27.1%. The phase composition of the green body layer is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.591, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 90.5°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 91.5°, and the static water contact angle after the firmness test is 90.2°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 8
[0147] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 258.74%, Al 2 O 3 23.70%, Fe 2 O 3 0.26%, CaO 4.77%, MgO2.45%, K 2 O 3.44%, Na 2 O 1.34%, loss on ignition 5.13%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1171°C, the firing cycle is 129.6min, and the holding time at the highest firing temperature is 16.0min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T8, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 7.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 96.0°.
[0148] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:13.
[0149] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 10 ml / m 2 The drying and curing temperature for the drying and curing treatment is 95°C, and the drying and curing time is 110 minutes.
[0150] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: rock mud, wollastonite A, raw talc B, potassium feldspar B, pyrophyllite, kaolin B, calcined clay B, potassium feldspar A, and calcined bauxite B.
[0151] In step S1 , the ball milling system is an intermittent ball milling system.
[0152] In step S4, the decoration of the ceramic rock slab body is a combination of digital mold technology and glaze polishing technology.
[0153] In step S6, post-processing includes polishing and edge grinding.
[0154] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.71%, the specific gravity is 1.693 g / ml, and the flow rate is 19s of NK-2 Iwata viscosity cup.
[0155] In step S2, the moisture content of the ceramic rock slab green body powder is 5.9%, and the particle size is 47.1% of the 40-mesh residue.
[0156] In step S3, the pressure of the molding equipment during compression molding is 40.5 MPa.
[0157] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 62.05%, Al 2 O 3 25.01%, Fe 2 O 3 0.25%, CaO 5.08%, MgO 2.62%, K 2 O 3.46%, Na 2 O 1.32%, the balance is impurities.
[0158] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 78.11%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.00%, Al 2 O 3 23.52%, Fe 2 O 3 0.32%, CaO 3.92%, MgO 2.84%, K 2 O 4.43%, Na 2 O 1.69%, TiO 2 0.28%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2O) is 0.655, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 93.5°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 94.2°, and the static water contact angle after the firmness test is 92.7°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 9
[0159] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 60.56%, Al 2 O 3 22.69%, Fe 2 O 3 0.27%, CaO 4.23%, MgO2.34%, K 2 O 4.80%, Na 2 O 0.85%, loss on ignition 4.01%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1164°C, the firing cycle is 136.4 minutes, and the holding time at the highest firing temperature is 14.7 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, thereby obtaining a ceramic rock plate product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, which is recorded as T9. The phase composition of the body layer contains crystalline silicon dioxide SiO 2 (C p ) has a weight percentage of 7.2%, and the static water contact angle of the hydrophobic self-cleaning coating is 94.9°.
[0160] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:14.5.
[0161] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 8 ml / m 2 The drying and curing temperature for the drying and curing treatment is 95°C, and the drying and curing time is 115 minutes.
[0162] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina A, and kaolin B.
[0163] In step S1 , the ball milling system is a continuous ball milling system.
[0164] In step S4, the decoration of the ceramic rock slab body is a combination of a rough and matte dry grain surface process and a dry grain polishing process.
[0165] In step S6, post-processing includes polishing and edge grinding.
[0166] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.64%, the specific gravity is 1.689 g / ml, and the flow rate is 18s of the NK-2 Iwata viscosity cup.
[0167] In step S2, the moisture content of the ceramic rock slab green body powder is 5.8%, and the particle size is 46.4% after 40 mesh sieve.
[0168] In step S3, the pressure of the molding equipment during compression molding is 41.0 MPa.
[0169] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 63.09%, Al 2 O 3 23.64%, Fe 2 O3 0.28%, CaO 4.41%, MgO 2.44%, K 2 O 5.00%, Na 2 O 0.89%, the remainder is impurities.
[0170] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 77.91%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 64.10%, Al 2 O 3 20.82%, Fe 2 O 3 0.35%, CaO 4.16%, MgO 2.88%, K 2 O 6.26%, Na 2 O 1.11%, TiO 2 0.31%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.634, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 92.7°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 93.4°, and the static water contact angle after the firmness test is 91.8°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 10
[0171] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 57.66%, Al 2 O 3 23.26%, Fe 2 O 3 0.23%, CaO 4.58%, MgO2.53%, K 2 O 3.06%, Na 2O 1.18%, loss on ignition 6.48%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1193°C, the firing cycle is 109.3min, and the holding time at the highest firing temperature is 13.4min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and solidified to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T10, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 7.3% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 121.0°.
[0172] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:10.
[0173] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 27 ml / m 2 The drying and curing temperature for the drying and curing treatment is 125°C, and the drying and curing time is 80 minutes.
[0174] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, wollastonite B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, bone ash, and calcined bauxite A.
[0175] In step S1 , the ball milling system is an intermittent ball milling system.
[0176] In step S2, the ceramic rock slab green body slurry obtained in step S1 is subjected to slurry preheating treatment before being spray-dried.
[0177] In step S4, the ceramic rock slab body is decorated by a sunken glaze / ink process.
[0178] In step S6, post-processing includes polishing and edge grinding.
[0179] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.93%, the specific gravity is 1.706 g / ml, and the flow rate is 23s of NK-2 Iwata viscosity cup.
[0180] In step S2, the moisture content of the ceramic rock slab green body powder is 6.4%, and the particle size is 49.3% of the 40-mesh residue.
[0181] In step S3, the pressure of the molding equipment during compression molding is 39.0 MPa.
[0182] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 62.16%, Al 2 O 3 24.95%, Fe 2 O 3 0.40%, CaO 4.73%, MgO 2.97%, K 2 O 3.29%, Na 2 O 1.17%, the balance is impurities.
[0183] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 77.51%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.09%, Al 2 O 3 23.12%, Fe 2 O 3 0.51%, CaO 3.45%, MgO 3.65%, K 2 O 4.25%, Na 2 O 1.51%, TiO 2 0.41%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2O) is 0.687, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 118.9°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 119.6°, and the static water contact angle after the firmness test is 117.9°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Embodiment 11
[0184] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 60.28%, Al 2 O 3 21.69%, Fe 2 O 3 0.19%, CaO 4.89%, MgO1.65%, K 2 O 3.79%, Na 2 O 1.07%, loss on ignition 5.59%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1207°C, the firing cycle is 95.7 minutes, and the holding time at the highest firing temperature is 12.1 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T11, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 7.5% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 124.4°.
[0185] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:9.5.
[0186] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 29 ml / m 2 The drying and curing temperature for the drying and curing treatment is 130°C, and the drying and curing time is 65 minutes.
[0187] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0188] In step S1 , the ball milling system is a continuous ball milling system.
[0189] In step S4, the ceramic rock slab body is decorated with a rough matt dry grain process.
[0190] In step S6, post-processing includes polishing and edge grinding.
[0191] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.07%, the specific gravity is 1.714 g / ml, and the flow rate is 25s of NK-2 Iwata viscosity cup.
[0192] In step S2, the moisture content of the ceramic rock slab green body powder is 6.6%, and the particle size is 50.7% of the 40-mesh residue.
[0193] In step S3, the pressure of the molding equipment during compression molding is 38.0 MPa.
[0194] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 63.91%, Al 2 O 3 23.50%, Fe 2 O 30.32%, CaO 4.78%, MgO 1.97%, K 2 O 4.03%, Na 2 O 1.37%, the balance is impurities.
[0195] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 77.31%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 65.40%, Al 2 O 3 21.77%, Fe 2 O 3 0.41%, CaO 3.08%, MgO 2.19%, K 2 O 5.22%, Na 2 O 1.77%, TiO 2 0.16%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.566, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 122.2°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 122.6°, and the static water contact angle after the firmness test is 120.3°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Example 12
[0196] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 55.68%, Al 2 O 3 27.36%, Fe 2 O 3 2.88%, CaO 0.48%, MgO4.80%, K 2 O 1.44%, Na 2O 2.78%, loss on ignition 4.00%, the balance is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1229°C, the firing cycle is 75.4 minutes, and the holding time at the highest firing temperature is 10.9 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T12, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 7.8% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 152.7°.
[0197] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:6.
[0198] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 45 ml / m 2 The drying and curing temperature for the drying and curing treatment is 145°C, and the drying and curing time is 25 minutes.
[0199] In step S1, the raw materials for preparing ceramic rock slab green body slurry are: ball clay A, washed soil A, washed soil B, wollastonite A, potassium-sodium feldspar B, raw talc A, potassium feldspar B, and calcined bauxite B.
[0200] In step S1 , the ball milling system is an intermittent ball milling system.
[0201] In step S4, the ceramic rock slab body is decorated by a glue dry granulation process.
[0202] In step S6, post-processing includes polishing and edge grinding.
[0203] In step S1, an 80-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.29%, the specific gravity is 1.727 g / ml, and the flow rate is NK-2 Iwata viscosity cup 29s.
[0204] In step S2, the moisture content of the ceramic rock slab green body powder is 7.1%, and the particle size is 52.9% of the 40-mesh residue.
[0205] In step S3, the pressure of the molding equipment during compression molding is 36.5 MPa.
[0206] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 58.00%, Al 2 O 3 28.50%, Fe 2 O 3 3.00%, CaO 0.50%, MgO 5.00%, K 2 O 1.50%, Na 2 O 2.90%, the remainder is impurities.
[0207] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 77.07%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 59.98%, Al 2 O 3 23.75%, Fe 2 O 3 2.64%, CaO 0.65%, MgO 6.49%, K 2 O 1.95%, Na 2 O 3.76%, TiO 2 0.78%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.681, the static water contact angle of the hydrophobic self-cleaning coating is 149.5° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 150.8°, and the static water contact angle is 148.6° after the firmness test again, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Embodiment 13
[0208] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 62.00%,Al 2 O 3 22.38%, Fe 2 O 3 0.05%, CaO 4.04%, MgO1.81%, K 2 O 3.85%, Na 2 O 1.12%, loss on ignition 4.62%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab, wherein the highest firing temperature of the high temperature firing is 1221°C, the firing cycle is 82.1min, and the holding time at the highest firing temperature is 9.6min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and cured to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T13, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 8.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 151.9°.
[0209] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:6.5.
[0210] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 45 ml / m 2 The drying and curing temperature for the drying and curing treatment is 145°C, and the drying and curing time is 30 minutes.
[0211] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and fused quartz.
[0212] In step S1 , the ball milling system is a continuous ball milling system.
[0213] In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment.
[0214] In step S4, the ceramic rock slab blank is decorated by a digital mold process.
[0215] In step S6, post-processing includes polishing and edge grinding.
[0216] In step S1, a 100-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 3.21%, the specific gravity is 1.723 g / ml, and the flow rate is NK-2 Iwata viscosity cup 27s.
[0217] In step S2, the moisture content of the ceramic rock slab green body powder is 6.9%, and the particle size is 52.1% of the 40-mesh residue.
[0218] In step S3, the pressure of the molding equipment during compression molding is 37.0 MPa.
[0219] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 65.00%, Al 2 O 3 23.46%, Fe 2 O 3 0.05%, CaO 4.24%, MgO 1.90%, K 2 O 4.04%, Na 2 O 1.17%, the remainder is impurities.
[0220] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 76.91%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO2 (A) 67.00%, Al 2 O 3 21.51%, Fe 2 O 3 0.06%, CaO 2.53%, MgO 1.95%, K 2 O 5.26%, Na 2 O 1.52%, TiO 2 0.18%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.539, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 148.7°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 150.1°, and the static water contact angle after the firmness test is 148.0°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Embodiment 14
[0221] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 57.98%, Al 2 O 3 22.63%, Fe 2 O 3 0.12%, CaO 6.10%, MgO3.82%, K 2 O 1.63%, Na 2 O 0.33%, loss on ignition 7.00%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a semi-finished ceramic rock slab. The highest firing temperature of the high temperature firing is 1157°C, the firing cycle is 143.2 minutes, and the holding time at the highest firing temperature is 8.3 minutes; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the ceramic rock slab semi-finished product after post-processing in step S6, and then dried and solidified to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock slab finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T14, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 8.5% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 93.8°.
[0222] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:15.
[0223] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 7 ml / m 2 The drying and curing temperature for the drying and curing treatment is 90°C, and the drying and curing time is 115 minutes.
[0224] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0225] In step S1 , the ball milling system is an intermittent ball milling system.
[0226] In step S4, the decoration of the ceramic rock slab body is a combination of a glue dry particle process and a peeling glaze / ink process.
[0227] In step S6, post-processing includes polishing and edge grinding.
[0228] In step S1, a 150-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 2.57%, the specific gravity is 1.684 g / ml, and the flow rate is 17s of the NK-2 Iwata viscosity cup.
[0229] In step S2, the moisture content of the ceramic rock slab green body powder is 5.6%, and the particle size is 45.7% of the 40-mesh residue.
[0230] In step S3, the pressure of the molding equipment during compression molding is 41.5 MPa.
[0231] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 62.34%, Al 2 O 3 24.33%, Fe 2 O 3 0.13%, CaO 6.56%, MgO 4.11%, K 2 O 1.75%, Na 2 O 0.35%, the balance is impurities.
[0232] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 70.00%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.88%, Al 2 O 3 21.84%, Fe 2 O 3 0.19%, CaO 5.50%, MgO 5.00%, K 2 O 2.50%, Na 2 O 0.50%, TiO 2 0.60%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.866, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 91.0°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 92.5°, and the static water contact angle after the firmness test is 90.8°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Embodiment 15
[0233] S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic slab green body powder: spray drying the ceramic slab green body slurry obtained in step S1, and then aging to obtain ceramic slab green body powder for pressing ceramic slab green body, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 60.11%, Al 2 O 3 22.30%, Fe 2 O 3 0.19%, CaO 5.45%, MgO4.09%, K 2 O 1.46%, Na 2 O 0.40%, loss on ignition 5.82%, the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: glazing and inkjet printing the ceramic rock slab body obtained in step S3, and then drying the ceramic rock slab body to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1200°C, the firing cycle is 102.5min, and the holding time at the highest firing temperature is 7.0min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: the hydrophobic self-cleaning coating solution prepared in S7 is uniformly sprayed on the upper surface of the semi-finished ceramic rock plate after post-processing in step S6, and then dried and solidified to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, to obtain a ceramic rock plate finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, denoted as T15, and the phase composition of the body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 10.0% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is 122.6°.
[0234] In step S7, a hydrophobic self-cleaning coating solution is formed, and the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:10.
[0235] In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 27 ml / m 2The drying and curing temperature for the drying and curing treatment is 125°C, and the drying and curing time is 75 minutes.
[0236] In step S1, the raw materials for preparing the ceramic rock slab green body slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0237] In step S1 , the ball milling system is a continuous ball milling system.
[0238] In step S4, the ceramic rock slab body is decorated by a peeling glaze / ink process.
[0239] In step S6, post-processing includes polishing and edge grinding.
[0240] In step S1, a 120-mesh vibrating screen is used for screening, the processing fineness of the ceramic rock slab green body slurry is 325 mesh with a sieve residue of 3.00%, the specific gravity is 1.710 g / ml, and the flow rate is 24s of the NK-2 Iwata viscosity cup.
[0241] In step S2, the moisture content of the ceramic rock slab green body powder is 6.5%, and the particle size is 50.0% of the 40-mesh residue.
[0242] In step S3, the pressure of the molding equipment during compression molding is 38.5 MPa.
[0243] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 63.83%, Al 2 O 3 23.68%, Fe 2 O 3 0.20%, CaO 5.79%, MgO 4.34%, K 2 O 1.55%, Na 2 O 0.42%, the remainder is impurities.
[0244] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 69.00%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 64.93%, Al 2 O 3 21.74%, Fe 2 O 3 0.29%, CaO 4.57%, MgO 5.33%, K 2 O 2.25%, Na 2 O 0.61%, TiO 20.28%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.864, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 120.6°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 121.1°, and the static water contact angle after the firmness test is 119.5°, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. Comparative Example Comparative Example 1
[0245] The same as Example 15, except that the raw material ratio for preparing the ceramic slab green body slurry is different, denoted as D1. In step S2, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 63.97%, Al 2 O 3 23.55%, Fe 2 O 3 0.39%, CaO 0.47%, MgO 0.11%, K 2 O 1.39%, Na 2 O 5.53%, loss on ignition 4.30%, and the remainder are impurities.
[0246] In step S8, the phase composition of the green body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 10.1% by weight.
[0247] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 66.84%, Al 2 O 3 24.61%, Fe 2 O 3 0.41%, CaO 0.49%, MgO 0.11%, K 2 O 1.45%, Na 2 O 5.78%, the remainder is impurities.
[0248] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 68.53%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 69.00%, Al 2 O 320.09%, Fe 2 O 3 0.60%, CaO 0.57%, MgO 0.16%, K 2 O 2.12%, Na 2 O 7.01%, TiO 2 0.45%, the silicon dioxide SiO in the glass phase exceeds the stoichiometric amount of feldspar in the phase composition of the green body layer. 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.095. Comparative Example 2 SiO 2 65.73%、Al 2 O 3 19.55%, Fe 2 O 3 0.33%, CaO 1.52%, MgO 0.48%, K 2 O2.88%, Na 2 O 2.78%, loss on ignition 6.46%, and the remainder are impurities.
[0249] In step S8, the phase composition of the green body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 21.7% by weight.
[0250] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 70.27%, Al 2 O 3 20.91%, Fe 2 O 3 0.35%, CaO 1.63%, MgO 0.51%, K 2 O 3.08%, Na 2 O 2.97%, the remainder is impurities.
[0251] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 65.60%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 67.76%, Al 2 O 3 19.13%, Fe 2 O 3 0.53%, CaO 2.35%, MgO 0.78%, K 2O 4.69%, Na 2 O 4.32%, TiO 2 0.43%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.340. Comparative Example 3
[0252] The same as Example 3, except that the raw material ratio for preparing the ceramic slab green body slurry is different, denoted as D3. In step S2, the chemical composition of the ceramic slab green body powder in terms of dry weight percentage includes: SiO 2 67.82%, Al 2 O 3 20.59%, Fe 2 O 3 0.20%, CaO 0.33%, MgO 0.22%, K 2 O 4.82%, Na 2 O 0.87%, loss on ignition 4.79%, and the remainder are impurities.
[0253] In step S8, the phase composition of the green body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 28.6% by weight.
[0254] The chemical composition of the green body layer by weight percentage includes: SiO 2 (T) 71.23%, Al 2 O 3 21.62%, Fe 2 O 3 0.21%, CaO 0.34%, MgO 0.23%, K 2 O 5.06%, Na 2 O 0.91%, the remainder is impurities.
[0255] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 58.70%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 66.47%, Al 2 O 3 21.38%, Fe 2 O 3 0.35%, CaO 0.58%, MgO 0.40%, K2 O 8.62%, Na 2 O 1.53%, TiO 2 0.67%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the body layer is 26.5%. The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.149. Comparative Example 4
[0256] Same as Example 15, except that the holding time at the highest firing temperature is 6.0 min, denoted as D4. In step S8, the phase composition of the green body layer is crystalline silicon dioxide SiO 2 (C p ) has a content of 12.0% by weight.
[0257] In step S8, the content of the glass phase in the phase composition of the green body layer by weight percentage is 67.02%, and the chemical components of the glass phase in the phase composition of the green body layer by weight percentage include: SiO 2 (A) 63.90%, Al 2 O 3 22.34%, Fe 2 O 3 0.30%, CaO 4.77%, MgO 5.47%, K 2 O 2.31%, Na 2 O 0.63%, TiO 2 0.28%, the glass phase in the phase composition of the green body exceeds the silicon dioxide SiO provided by the feldspar stoichiometry 2 The percentage of the substance in the glass phase is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.865. Comparative Example 5
[0258] Same as Example 2, except that the spraying amount of the hydrophobic self-cleaning coating solution is 52 ml / m 2 , denoted as D5, in step S8, the static water contact angle of the hydrophobic self-cleaning coating is 159.6°.
[0259] In step S8, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 156.4°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 157.2°, and the static water contact angle after the firmness test is 155.7°. The hydrophobic self-cleaning coating is qualified in the pollution resistance test. Comparative Example 6
[0260] The same as Example 2, except that the hydrophobic self-cleaning coating solution for forming the hydrophobic self-cleaning coating has a ratio of aluminate solid to anhydrous ethanol of 1:4 in parts by weight, denoted as D6. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 86.7°.
[0261] In step S8, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 83.4°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 85.0°, and the static water contact angle after the firmness test is 83.1°. The hydrophobic self-cleaning coating fails the pollution resistance test. Comparative Example 7
[0262] The same as Example 2, except that the drying and curing temperature for the drying and curing treatment is 155° C., denoted as D7. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 79.2°.
[0263] In step S8, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 77.5°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 78.5°, and after the firmness test again, the static water contact angle is 76.9°. The hydrophobic self-cleaning coating fails the pollution resistance test. Comparative Example 8
[0264] Same as Example 2, except that the drying and curing time is 10 min, denoted as D8. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 155.6°.
[0265] In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 85.4° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 87.3°, and the static water contact angle is 83.1° after the firmness test again. The hydrophobic self-cleaning coating is qualified in the pollution resistance test. Comparative Example 9
[0266] Same as Example 2, except that the spraying amount of the hydrophobic self-cleaning coating solution is 4 ml / m 2 , denoted as D9, in step S8, the static water contact angle of the hydrophobic self-cleaning coating is 88.1°.
[0267] In step S8, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 86.2°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 86.9°, and the static water contact angle after the firmness test is 85.4°. The hydrophobic self-cleaning coating fails the pollution resistance test. Comparative Example 10
[0268] The same as Example 2, except that the hydrophobic self-cleaning coating solution for forming the hydrophobic self-cleaning coating has a ratio of aluminate solid to anhydrous ethanol in parts by weight of 1:16, denoted as D10. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 88.9°.
[0269] In step S8, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is 86.6°, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 87.9°, and the static water contact angle after the firmness test is 86.1°. The hydrophobic self-cleaning coating fails the pollution resistance test. Comparative Example 11
[0270] The same as Example 2, except that the drying and curing temperature for the drying and curing treatment is 85° C., denoted as D11. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 91.5°.
[0271] In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 84.7° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 85.4°, and the static water contact angle is 84.0° after the firmness test again. The hydrophobic self-cleaning coating is qualified in the pollution resistance test. Comparative Example 12
[0272] Same as Example 2, except that the drying and curing time is 125 min, denoted as D12. In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 93.2°.
[0273] In step S8, the static water contact angle of the hydrophobic self-cleaning coating is 91.8° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is 92.1°, and the static water contact angle is 91.2° after the firmness test again. The hydrophobic self-cleaning coating is qualified in the pollution resistance test. Performance Test Example
[0274] The ceramic rock slabs manufactured in Examples 1-15 (T1-T15) and Comparative Examples 1-12 (D1-D12) were respectively subjected to the following performance tests according to the following standards, and the results are shown in Table 1 below.
[0275] Table 1 Ceramic rock plate performance test results T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 T12 T13 T14 T15 <![CDATA[SiO 2 (C p )(wt%)]]> 0.0 2.0 3.0 4.0 4.5 6.5 6.7 7.0 7.2 7.3 7.5 7.8 8.0 8.5 10.0 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 2.00 1.94 1.89 1.83 1.77 1.71 1.66 1.60 1.54 1.49 1.43 1.37 1.31 1.26 1.20 Modulus of rupture (MPa) 100.0 96.4 92.9 89.3 85.7 82.1 78.6 75.0 71.4 67.9 64.3 60.7 57.1 53.6 50.0 Machinability Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Static water contact angle of hydrophobic self-cleaning coating 126.6 158.3 97.8 155.5 154.6 119.3 92.6 96.0 94.9 121.0 124.4 152.7 151.9 93.8 122.6 Static water contact angle of hydrophobic self-cleaning coating after fastness test 123.9 155.1 95.1 152.2 151.3 117.3 90.5 93.5 92.7 118.9 122.2 149.5 148.7 91.0 120.6 Static water contact angle of hydrophobic self-cleaning coating after durability testing 124.3 156.5 96.6 153.1 152.7 118.6 91.5 94.2 93.4 119.6 122.6 150.8 150.1 92.5 121.1 Static water contact angle of hydrophobic coating after durability test and firmness test again 122.4 154.7 93.6 151.9 150.4 116.3 90.2 92.7 91.8 117.9 120.3 148.6 148.0 90.8 119.5 Pollution resistance test qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified qualified (Continued Table 1) D1 D2 D3 D4 D5 D6 D7 D8 D9 D10 D11 D12 <![CDATA[SiO 2 (C p )(wt %)]]> 10.1 21.7 28.6 12.0 3.0 3.0 3.0 3.0 3.0 3.0 3.0 3.0 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 1.18 0.94 0.79 1.12 1.89 1.89 1.89 1.89 1.89 1.89 1.89 1.89 Modulus of rupture (MPa) 48.2 39.5 37.2 45.7 92.9 92.9 92.9 92.9 92.9 92.9 92.9 92.9 Machinability Level 2 Level 3 Level 3 Level 2 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Static water contact angle of hydrophobic self-cleaning coating 122.6 154.6 97.8 122.6 159.6 86.7 79.2 155.6 88.1 88.9 91.5 93.2 Static water contact angle of hydrophobic self-cleaning coating after fastness test 120.6 151.3 95.1 120.6 156.4 83.4 77.5 85.4 86.2 86.6 84.7 91.8 Static water contact angle of hydrophobic self-cleaning coating after durability testing 121.1 152.7 96.6 121.1 157.2 85.0 78.5 87.3 86.9 87.9 85.4 92.1 Performance Test Example 1
[0276] Fracture toughness: The indentation method is used for testing. The specific process is as follows: The surface of the test sample is first polished to a mirror surface. On a microhardness tester, a 10kg load is applied to the polished surface with a conical diamond indenter of the hardness tester to produce an indentation. This creates prefabricated cracks at the four vertices of the indentation. The fracture toughness value (K IC ). The calculation formula is:
[0277] Among them, Young's modulus E is in GPa, load P is in N, crack length C is in mm, microhardness H is V The unit is GPa.
[0278] Modulus of rupture: The modulus of rupture is determined according to GB / T 3810.4-2016 "Test methods for ceramic tiles Part 4: Determination of modulus of rupture and breaking strength".
[0279] Machinability: Processing shall be carried out in accordance with the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard. Performance Test Example 2
[0280] Firmness test: Under constant pressure, use a brush (the hair in the brush is made of defatted pig bristles, with a length of 45mm and a thickness of 12mm) to cyclically brush the surface of the hydrophobic self-cleaning coating. The brush is perpendicular to the surface of the hydrophobic self-cleaning coating. After the firmness test is carried out for 1000 cycles, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is measured.
[0281] Durability test: The manufactured ceramic rock slab is placed in the air for 180 days, and the static water contact angle of the hydrophobic self-cleaning coating is measured after the durability test. The color change of the hydrophobic self-cleaning coating before and after the test is compared. If color change occurs, it is considered unqualified, otherwise it is considered qualified, and a firmness test is performed again to measure the static water contact angle of the hydrophobic self-cleaning coating.
[0282] Pollution resistance test: Apply blue ink, marker pen and paint pen on the surface of the manufactured ceramic rock slab respectively, and place the ceramic rock slab in the air for 7 days. Wipe it with a semi-dry towel (no water can be wrung out). If all three pollutants can be wiped off and there is no trace on the surface of the ceramic rock slab, it is considered qualified.
[0283] In this application, the phase composition of the green body layer of the ceramic rock plate is crystalline silicon dioxide SiO 2 (C p ) It is most intuitive to determine whether the ceramic rock plate is environmentally friendly by measuring the content by weight percentage. From the above table, it can be seen that the crystalline silicon dioxide SiO 2 (C p ) by weight percentage is 10% or less. Whether in the early stage of ceramic slab raw material processing or in the later stage of ceramic slab product cutting, grinding and other processing, it will not produce a lot of high crystalline silicon dioxide content respirable dust, which effectively reduces the risk of silicosis in the process of ceramic slab manufacturing and processing. In addition, due to the crystalline silicon dioxide SiO 2 (C p ) is low in content by weight percentage, the stress generated by the crystal transformation of silicon dioxide in the ceramic rock plate is small, the machinability of the ceramic rock plate reaches the first level, and the loss caused by the cracking of the ceramic rock plate during the later cold working will also be small. The ceramic rock plates D1-D4 manufactured in comparative examples 1-4 are manufactured according to the process conditions of Example 15, Example 5, Example 3, and Example 15, respectively. However, since the raw materials for preparing the ceramic rock plate blank slurry of D1, D2, D3 and T15, T5, and T3 are the same but in different proportions, and the holding time at the highest firing temperature of D4 and T15 is different, the crystalline silicon dioxide SiO 2 (C p ) are all higher than 10% by weight, and the risk of silicosis is high during the manufacturing and processing of ceramic rock panels. Secondly, due to the phase composition of the green layer of ceramic rock panels D1-D4, the crystalline silicon dioxide SiO 2 (C p ) has a high content in terms of weight percentage, and the stress generated by the crystal transformation of silicon dioxide in the ceramic rock slab is relatively large. The machinability of the ceramic rock slab has not reached the first level, and the loss caused by the cracking of the ceramic rock slab during the later cold processing is also large. The above data objectively reflect that the ceramic rock slab manufactured by this application has been significantly improved in terms of environmental protection and processing performance. In particular, the ceramic rock slab product manufactured in Example 1 will not produce respirable dust with a high crystalline silicon dioxide content during the cutting, grinding and other processing processes, and the risk of suffering from silicosis is very low. It also has good toughness, high strength and good machinability.
[0284] Fracture toughness and fracture modulus are the most important data that determine the high toughness, high strength and machinability of ceramic rock plates. From the above table, it can be seen that the fracture toughness of ceramic rock plates T1-T15 manufactured in Examples 1-15 is all within 1.20 MPa·m 1 / 2and above, the modulus of rupture is 50 MPa and above, and the machinability is first-class. The difference between D1 manufactured in Comparative Example 1 according to the process conditions of Example 15 and T15 is that the raw material ratio for preparing the ceramic rock slab green body slurry is different, and the content of the glass phase in the phase composition of the green body layer is 68.53% by weight, which is lower than 69.00%. The glass phase is relatively small, and there is not enough glass phase to stick to the crystalline phase. The bonding force between the crystalline phases is low, resulting in the fracture toughness of D1 being less than 1.20 MPa·m 1 / 2 , the modulus of rupture is less than 50MPa, and secondly, the corresponding crystalline silicon dioxide SiO 2 (C p ) is higher than 10% by weight. During the firing process, the crystalline silicon dioxide undergoes a crystal phase transformation and generates a large stress, resulting in the machinability reaching only level 2. Comparative Examples 2 and 3 are respectively manufactured according to the process conditions of Example 5 and Example 3. D2 and D3 are different from T5 and T3 in that the raw materials for preparing the ceramic rock slab green body slurry are the same but the proportions are different. In the phase composition of the green body layer of D2, the glass phase has n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.340 and lower than 0.350. In the phase composition of the body layer of D3, the glass phase contains more silicon dioxide SiO than the feldspar stoichiometrically provided 2 The amount percentage of the substance in (E) is 26.5%, which is lower than 27.0%. The corresponding phase composition of the green body layer of D3 is n(CaO+MgO) / n(CaO+MgO+K 2 O+Na 2 O) is 0.149 and lower than 0.350, which results in insufficient solubility of glass relative to crystalline silicon dioxide in the phase composition of the green body layer during the firing process of the ceramic rock plate, causing a small amount of crystalline silicon dioxide SiO 2 (C r ) is not very good at being converted into amorphous silicon dioxide and silicon dioxide that exists as a component in other crystalline phases except crystalline silicon dioxide. Therefore, the crystalline silicon dioxide SiO 2 (C p ) is higher in weight percentage, and the corresponding machinability level is lower, only level 3; Comparative Example 4 D4 manufactured according to the process conditions of Example 15 is different from T15 in that the holding time at the highest firing temperature is 6 min, which is lower than 7 min. Due to the insufficient holding time at the highest firing temperature, on the one hand, a small amount of crystalline silicon dioxide SiO 2 (C r) does not have enough time to transform into the glass phase and the silica that exists as a component in other crystalline phases except crystalline silica. On the other hand, it is not conducive to the oxidative decomposition of humus in the ceramic rock slab blank, which leads to a decrease in the density of the blank layer. Therefore, the fracture toughness and rupture modulus of D4 are lower than those of T15, and the machinability only reaches level 2. This fully demonstrates the feasibility of the scheme for improving the machinability of ceramic rock slabs in this application and the obvious advantages of machinability.
[0285] In the present application, the hydrophobic self-cleaning coating of the manufactured ceramic rock plate is measured by measuring the static water contact angle of the hydrophobic self-cleaning coating, and conducting a firmness test, a durability test, and a pollution resistance test to judge the hydrophobic self-cleaning, firmness and other properties of the hydrophobic self-cleaning coating most intuitively. It can be seen from the above table that the static water contact angle of the hydrophobic self-cleaning coating of the ceramic rock plate T1-T15 manufactured in Examples 1-15 is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is greater than 90°, and the hydrophobic self-cleaning coating does not change color or static after the durability test. The water contact angle is greater than 90° and the static water contact angle is greater than 90° after the firmness test, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test. When used in humid, complex and changeable environments such as bathrooms, kitchens, and building exterior walls, it is not easy to be damaged or fall off during use. It has good adhesion and high firmness, and is not easy to react with water, oxygen, carbon dioxide, etc. in the air to change color and lose the hydrophobic self-cleaning function. It has good durability. After being coated with blue ink, markers, and paint pens and left to stand for 7 days, it can be wiped off with a semi-dry towel without leaving any traces, and has good pollution resistance. Although the ceramic rock panels D5-D8 and D9-D12 manufactured in Comparative Examples 5-8 and 9-12 are manufactured according to the process conditions of Example 2 and Example 7, respectively, D5 and D9 are different from T2 and T7 in that the spraying amount of the hydrophobic self-cleaning coating solution is different. The spraying amount of the hydrophobic self-cleaning coating solution of D5 is 52ml / m 2 , higher than 50ml / m 2 Although the static water contact angle of the prepared hydrophobic self-cleaning coating is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the durability test is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the durability test is again greater than 90°, and the pollution resistance test is qualified, the excessive spraying amount leads to a thicker hydrophobic self-cleaning coating, thereby affecting the decorative effect of the ceramic rock slab decorative layer. Although the manufactured ceramic rock slab has good hydrophobic cleaning ability, the decorative effect is not good; the spraying amount of the hydrophobic self-cleaning coating solution of D9 is 4ml / m 2 , less than 5ml / m 2, the spraying amount is insufficient to form a complete hydrophobic self-cleaning coating, resulting in a static water contact angle of the hydrophobic self-cleaning coating of less than 90° and failure in the pollution resistance test. D6 and D10 are different from T2 and T7 respectively in that the hydrophobic self-cleaning coating solution forming the hydrophobic self-cleaning coating has different ratios of aluminate solids to anhydrous ethanol in parts by weight. The hydrophobic self-cleaning coating solution forming the hydrophobic self-cleaning coating of D6 has a ratio of aluminate solids to anhydrous ethanol in parts by weight of 1:4, which is higher than 1:5. The concentration of the hydrophobic self-cleaning coating solution is too high. During the spraying process, the hydrophobic self-cleaning coating solution is prone to agglomeration on the upper surface of the decorative layer, and the formed hydrophobic self-cleaning coating is uneven, resulting in a static water contact angle of the prepared hydrophobic self-cleaning coating. The hydrophobic self-cleaning coating solution of D10, which forms a hydrophobic self-cleaning coating, has a ratio of aluminate solid to anhydrous ethanol of 1:16 in parts by weight, which is lower than 1:15. The concentration of the hydrophobic self-cleaning coating solution is too low, and the spraying is uneven, so that a complete hydrophobic self-cleaning coating cannot be formed on the upper surface of the decorative layer. As a result, the static water contact angle of the prepared hydrophobic self-cleaning coating is less than 90° and the pollution resistance test fails. In addition, the content of anhydrous ethanol in the hydrophobic self-cleaning coating solution is relatively high, and manufacturing accidents are prone to occur after volatilization in a relatively small space. D7 and D11 are different from T2 and T7 respectively in that the drying and curing temperatures for the drying and curing treatment are different. The drying and curing temperature for D7 is 155°C, which is higher than 150°C. The excessively high drying and curing temperature causes the hydrophobic self-cleaning coating solution to turn yellow, and the prepared hydrophobic self-cleaning coating affects the surface decorative effect of the ceramic rock slab. In addition, due to the oxidation and other deterioration of the effective ingredients of the hydrophobic self-cleaning coating solution, the static water contact angle of the prepared hydrophobic self-cleaning coating is less than 90°, and the hydrophobic self-cleaning function is lost; the drying and curing temperature for D11 is 85°C, which is lower than 90°C. Although the static water contact angle of the prepared hydrophobic self-cleaning coating is 91.5°, which is greater than 90°, and the pollution resistance test is qualified, the drying and curing temperature is too low and the adhesion to the decorative layer is poor, so that a firm hydrophobic self-cleaning coating cannot be formed, resulting in a static water contact angle of the hydrophobic self-cleaning coating after the firmness test being less than 90°.D8 and D12 are different from T2 and T7 in that the drying and curing time is different. The drying and curing time of D8 is 10 minutes, which is less than 15 minutes. Although the static water contact angle of the prepared hydrophobic self-cleaning coating is 155.6°, which is greater than 90°, and the pollution resistance test is qualified, the drying and curing time is too short and the adhesion with the decorative layer is poor, so a firm hydrophobic self-cleaning coating cannot be formed, resulting in a static water contact angle of the hydrophobic self-cleaning coating after the firmness test less than 90°; the drying and curing time of D12 is The time is 125min and greater than 120min, the static water contact angle of the prepared hydrophobic self-cleaning coating is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the firmness test is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the durability test is greater than 90°, the static water contact angle of the hydrophobic self-cleaning coating after the durability test is again greater than 90°, and the pollution resistance test is qualified, but the drying and curing time is too long, which is not suitable for assembly line production, and the energy consumption is high, which does not meet the requirements of low-carbon and environmentally friendly production. The feasibility of the scheme for preparing the hydrophobic self-cleaning coating in this application is fully demonstrated.
[0286] According to the disclosure and guidance of the above description, those skilled in the art to which the present application belongs may also change and modify the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and the modification and change of the application should also fall within the protection scope of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.
Claims
1. An environmentally friendly ceramic rock plate with low crystalline silica content and hydrophobic self-cleaning function, characterized by: The invention comprises a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, wherein the phase composition of the body layer comprises crystalline silicon dioxide SiO2 (C p ) is ≤10% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is >90°.
2. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized by: The chemical composition of the green body layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, and the remainder is impurities.
3. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized in that: The decorative layer is made by any one of porcelain polishing process, glaze polishing process, dry particle polishing process, glue dry particle process, digital mold process, fine or coarse dry particle surface process, peeling glaze / ink or sinking glaze / ink process or a combination thereof.
4. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized in that: The hydrophobic self-cleaning coating solution for forming the hydrophobic self-cleaning coating has a ratio of aluminate solid to anhydrous ethanol of 1:(5-15) in parts by weight.
5. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized in that: After the firmness test, the static water contact angle of the hydrophobic self-cleaning coating is greater than 90°. After the durability test, the hydrophobic self-cleaning coating does not change color, the static water contact angle is greater than 90°, and after the firmness test again, the static water contact angle is greater than 90°. The hydrophobic self-cleaning coating is qualified in the pollution resistance test.
6. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized by: The content of the glass phase in the physical phase composition of the green body layer is 69.0%-88.5% by weight; the chemical components of the glass phase in the physical phase composition of the green body layer include: SiO2 (A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, TiO2 0-0.78%; the amount percentage of silicon dioxide SiO2 (E) in the glass phase in the physical phase composition of the green body layer that exceeds the stoichiometric ratio of feldspar is ≥27.0%; n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the green body layer is ≥0.
350.
7. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized by: The fracture toughness of the environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function is ≥1.2MPa·m 1 / 2 , modulus of rupture ≥50MPa.
8. The environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 1 is characterized by: The environmentally friendly ceramic rock slab with low crystalline silica content and hydrophobic self-cleaning function is processed according to the machinability test method in the T / CBCSA 40-2021 "Ceramic Rock Slab" standard to achieve first-level machinability.
9. A method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function, characterized in that: The following steps are involved: S1, preparation of ceramic rock slab green body slurry: firstly, raw materials for preparing ceramic rock slab green body slurry are weighed, then the weighed raw materials for preparing ceramic rock slab green body slurry are mixed, then water, ball stone and additives are added and ball milled through a ball milling system, and finally the ceramic rock slab green body slurry is obtained by sieving; S2, preparation of ceramic rock slab green body powder: spray drying the ceramic rock slab green body slurry obtained in step S1, and then aging to obtain ceramic rock slab green body powder for pressing ceramic rock slab green body, wherein the chemical composition of the ceramic rock slab green body powder in terms of dry weight percentage includes: SiO2 55.68%-62%, Al2O3 20.5%-27.36%, Fe2O3 0-2.88%, CaO0.48%-6.52%, MgO 0.47%-4.8%, K2O 1.44%-4.8%, Na2O 0.33%-2.8%, ignition loss 4%-7%, and the remainder is impurities; S3, preparation of ceramic rock slab green body: the ceramic rock slab green body powder obtained in step S2 is pressed into shape by a molding device and dried to obtain a ceramic rock slab green body; S4, decoration of the ceramic rock slab body: decorating the ceramic rock slab body obtained in step S3, and then drying it to obtain a decorated ceramic rock slab body; S5, firing of ceramic rock slab blank: firing the decorated ceramic rock slab blank obtained in step S4 at high temperature to obtain a ceramic rock slab semi-finished product, wherein the highest firing temperature of the high temperature firing is 1150-1250°C, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min; S6, post-processing of semi-finished ceramic rock slabs: post-processing of semi-finished ceramic rock slabs; S7, preparation of hydrophobic self-cleaning coating solution; S8, preparation of a hydrophobic self-cleaning coating: uniformly spraying the hydrophobic self-cleaning coating solution prepared in S7 on the upper surface of the ceramic rock slab semi-finished product after post-processing in step S6, and then drying and curing the product to form a hydrophobic self-cleaning coating on the upper surface of the decorative layer, thereby obtaining a ceramic rock slab finished product comprising a body layer, a decorative layer arranged on the upper surface of the body layer, and a hydrophobic self-cleaning coating arranged on the upper surface of the decorative layer, wherein the phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p ) is ≤10% by weight, and the static water contact angle of the hydrophobic self-cleaning coating is >90°.
10. The method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 9, characterized in that: In step S7, the hydrophobic self-cleaning coating solution is formed to form a hydrophobic self-cleaning coating, wherein the ratio of aluminate solid to anhydrous ethanol in parts by weight is 1:(5-15); The method for preparing the hydrophobic self-cleaning coating solution comprises the following steps: S7a(Ⅰ), crushing the aluminate solid: crushing the aluminate solid and sieving it with a 100-mesh sieve to obtain a granular aluminate solid powder less than 150 μm; S7a(Ⅱ), dissolving the aluminate solid: mixing the crushed aluminate solid powder with anhydrous ethanol in a certain proportion and stirring until the aluminate solid powder is completely dissolved to prepare a uniform hydrophobic self-cleaning coating solution; In step S8, the spraying amount of the hydrophobic self-cleaning coating solution is 5-50 ml / m 2 The drying and curing temperature of the drying and curing treatment is 90-150° C., and the drying and curing time is 15-120 minutes.
11. The method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 9, characterized in that: In step S1, when preparing black ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay A, washed soil A, washed soil B, kaolin A, calcined soil A, potassium feldspar A, potassium feldspar B, potassium sodium feldspar A, potassium sodium feldspar B, wollastonite A, raw talc A, raw talc B, calcined bauxite B, and diopside; when preparing white ceramic rock slab slurry, the raw materials for preparing the ceramic rock slab slurry are: ball clay B, rock mud, kaolin B, calcined soil B, raw talc B, wollastonite A, wollastonite B, potassium feldspar A, potassium feldspar B, pyrophyllite, TM2106 frit, fused quartz, calcined alumina A, calcined alumina B, bone ash, calcined bauxite A, and calcined bauxite B.
12. The method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 9, characterized in that: In step S1, the ball milling system is an intermittent ball milling system or a continuous ball milling system; In step S2, before spray drying the ceramic rock slab green body slurry obtained in step S1, the ceramic rock slab green body slurry is subjected to slurry preheating treatment; In step S4, the decoration of the ceramic rock slab body is any one of porcelain polishing process, glaze polishing process, dry grain polishing process, glue dry grain process, digital mold process, fine or coarse matte dry grain process, peeling glaze / ink or sinking glaze / ink process or a combination thereof; In step S6, the post-processing includes polishing and edge grinding.
13. The method for manufacturing an environmentally friendly ceramic rock plate with low crystalline silicon dioxide content and hydrophobic self-cleaning function according to claim 9, characterized in that: In step S1, the sieving is performed using a 80-150 mesh vibrating screen, the processing fineness of the ceramic rock slab green body slurry is 325 mesh, the residue is 2.5%-3.5%, the specific gravity is 1.68-1.74 g / ml, and the flow rate is NK-2 Iwata viscosity cup 16-32s; In step S2, the moisture content of the ceramic rock slab green body powder is 5.5%-7.5%, and the particle size is 45%-55% of the 40-mesh residue; In step S3, the pressure of the molding equipment during compression molding is 35-42 MPa; In step S8, the content of the glass phase in the phase composition of the green body layer is 69.0%-88.5% by weight, and the chemical components of the glass phase in the phase composition of the green body layer include: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, TiO2 0-0.78%, the amount percentage of silicon dioxide SiO2(E) in the glass phase in the physical phase composition of the body layer that exceeds the stoichiometric amount of feldspar is ≥27.0%, n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase in the physical phase composition of the body layer is ≥0.350, the static water contact angle of the hydrophobic self-cleaning coating is greater than 90° after the firmness test, the hydrophobic self-cleaning coating does not change color after the durability test, the static water contact angle is greater than 90°, and the static water contact angle is greater than 90° after the firmness test again, and the hydrophobic self-cleaning coating is qualified in the pollution resistance test.
Citation Information
Patent Citations
Outdoor ecological and environment-friendly ceramic tile with antibacterial and self-cleaning functions and preparation method of ceramic tile
CN106007688A
Ultra-white rock plate with fine processability and preparation method thereof
CN112321288A
Low-density elongated stone porcelain ceramic plate and preparation method thereof
CN113800880A
Anti-fouling waterproof ceramic rock plate and preparation method thereof
CN115057725A
Super -hydrophobic thermal -insulation decorative integrated board
CN207211573U
Cited By
Strong bonding surface glaze layer for antifouling ceramic tile as well as preparation method and application of strong bonding surface glaze layer
CN121021196A
A strongly bonded glaze layer for stain-resistant ceramic tiles, its preparation method and application
CN121021196B
Mirror-polished thin ceramic rock plate and preparation method thereof
CN121554307A
Mirror-polished thin ceramic rock plate and preparation method thereof
CN121554307B